Generasi Sehat Digital: Menavigasi Kewaspadaan Kesehatan Mental Dan Mengelola Kecanduan Gadget Di Kalangan Pelajar - Azniah Syam; Syaifuddin Zainal; Indra Dewi; Kartika Sari Wijayaningsih; Musni Musni (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Abstract and Keywords must be written Teens navigate a digital environment that never sleeps, leading to potential disruptions in sleep patterns and overall health. The use of gadgets is increasingly widespread, as is the increase in gadget addiction among teenagers. The aim of this activity is to create a school environment that supports teenagers' social development without triggering unhealthy gadget addiction. In this way, teenagers can be guided towards conscious and self-responsible behavior in using devices. The awareness and awareness campaign will focus on how students can recognize the dimensions of gadget addiction and some of the signs and symptoms of mental disorders. The method of conveying information is carried out in the classroom in the form of a focus group discussion. Before the campaign is carried out, students will be given the SAS and PHQ9 forms as basic measuring instruments that detect the possibility of potential gadget addiction and mental disorders. Based on the results of addiction scores and mental health disorders, it shows that there is a significant correlation between addiction scores and mental health disorder scores with a p value <0.037. Even though the magnitude of this relationship is very weak linearly, several dimensions have a fairly clear cause and effect path, thus providing confirmation that excessive exposure to the use of digital devices will threaten the health of adolescents.